2014
DOI: 10.1007/s12031-014-0354-z
|View full text |Cite
|
Sign up to set email alerts
|

Low-Level Laser Therapy Ameliorates Disease Progression in a Mouse Model of Alzheimer’s Disease

Abstract: Low-level laser therapy (LLLT) has been used to treat inflammation, tissue healing, and repair processes. We recently reported that LLLT to the bone marrow (BM) led to proliferation of mesenchymal stem cells (MSCs) and their homing in the ischemic heart suggesting its role in regenerative medicine. The aim of the present study was to investigate the ability of LLLT to stimulate MSCs of autologous BM in order to affect neurological behavior and β-amyloid burden in progressive stages of Alzheimer's disease (AD) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
72
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 94 publications
(74 citation statements)
references
References 44 publications
1
72
0
1
Order By: Relevance
“…They found that there was a highly beneficial effect on neurocognitive behavior with irradiation to the head, but nevertheless there was also a statistically significant (although less pronounced benefit, referred to by these authors as an ‘abscopal effect”) when the head was shielded from light [34]. Moreover Oron and co-workers [35] have shown that delivering NIR light to the mouse tibia (using either surface illumination or a fiber optic) resulted in improvement in a transgenic mouse model of Alzheimer’s disease (AD). Light was delivered weekly for 2 months, starting at 4 months of age (progressive stage of AD).…”
Section: Tissue Optics Light Delivery Light Sourcesmentioning
confidence: 99%
“…They found that there was a highly beneficial effect on neurocognitive behavior with irradiation to the head, but nevertheless there was also a statistically significant (although less pronounced benefit, referred to by these authors as an ‘abscopal effect”) when the head was shielded from light [34]. Moreover Oron and co-workers [35] have shown that delivering NIR light to the mouse tibia (using either surface illumination or a fiber optic) resulted in improvement in a transgenic mouse model of Alzheimer’s disease (AD). Light was delivered weekly for 2 months, starting at 4 months of age (progressive stage of AD).…”
Section: Tissue Optics Light Delivery Light Sourcesmentioning
confidence: 99%
“…The treatment significantly decreased Aβ area burden in the hippocampus and improved cognitive capacity and spatial learning of the AD mice compared to non-treated AD mice [9].…”
Section: Alzheimer's Diseasementioning
confidence: 85%
“…As a noninvasive treatment, accumulating evidence has shown that transcranial LLLT is a beneficial treatment for depression [4,5] and AD [10][11][12][13][14][15][16][17] in rodent models. In addition, transcranial LLLT has been carried out on depression and chronic TBI patients in preclinical trials [6][7][8]26,27].…”
Section: Conclusion and Perspectivementioning
confidence: 99%
“…Recently, researchers have shifted the focus of research to the application of LLLT on brain disorders [1][2][3]. During the past decade, LLLT has been widely used to study neurological and psychological diseases [3] such as depressionlike behaviors [4][5][6][7][8], Alzheimer's disease (AD) [9][10][11][12][13][14][15][16][17][18][19][20], Parkinson's disease [21], stroke [22,23] and traumatic brain injury (TBI) [24][25][26][27][28][29][30][31][32]. Because red or NIR light can effectively penetrate into brain tissues [33,34], it can be noninvasive and play a beneficial role in increasing ATP biosynthesis and neurogenesis [1,2].…”
Section: Introductionmentioning
confidence: 99%